Double pylorus in the era of proton pump inhibitors - Mansur Reimão, Sílvia; Ferreira De Souza, Thiago; Otoch, Jose P.; Makoto Sakai, Christiano; Yance Hurtado, Robin Mauricio; Menezes Marques, Lucas; Guimarães Hourneaux De Moura, Eduardo; Artifon, Everson L. A. (Revista de Gastroenterología del Perú, 2017)
Double pylorus and gastroduodenal fistula are rare conditions and can be either congenital or acquired. We report a case of a 58-year-old man with epigastric pain and dyspepsia in which the upper gastrointestinal endoscopy revealed an acquired double pylorus, probably caused by a gastric ulcer.